Combustion Assisted Synthesis of CuO Nanoparticles and Structure-Property Evaluation in nano-CuO Polymer Composites - Prasanth, Gopinath; Madhu, Gattumane Motappa; Kottam, Nagaraju (Applied Science and Engineering Progress, 2024)
Metal oxide-based nanoparticle as a filler in epoxy polymer composites has diverse applications in various industries, including adhesives, automobiles, aerospace, wind energy, and civil engineering. However, these composites must fulfill essential properties encompassing chemical, curing, optical, and thermal attributes. This study focuses on enhancing epoxy polymer by integrating copper oxide (CuO) nanoparticles synthesized through solution combustion. Varied CuO loadings (0.5–2.5 wt.%) were impregnated into the epoxy, critically impacting the structural attributes of the resulting nano-CuO polymer composites. Various material characterization techniques were employed to study the synthesized materials’ morphology, elemental composition, phase formation, identification of the presence of functional groups, thermal stability, and optical properties. SEM images show the presence of spherical particles with porous structures. EDX confirmed the presence of Cu and O elements, while the XRD pattern showed the formation of CuO with an average crystallite size of 46 nm. FTIR confirms the presence of O-H, C-H, and C=C functional groups. TGA showed thermal stability and revealed minimal mass loss below 250 °C for nano-CuO polymer composites and minimal mass loss occurred for CuO nanoparticles at 900 °C. Photoluminescence exhibited redshifted luminescence spectra. The study suggests improved qualities due to CuO nanoparticle integration into epoxy. CuO loading crucially influences nano-CuO polymer composite properties, rendering them ideal for high-temperature applications, supported by remarkable thermal stability evidenced by substantial residual mass in TGA.